Morte encefálica no paciente adulto: uma revisão integrativa da literatura - Pinheiro, Francisco Edes da Silva (2022)
Brain death can be defined as the irreversible state of brain functions, considering the cerebral hemispheres as well as the brainstem. Two tests are required that can confirm the absence or cessation of brain stem activities for diagnosis of ED in Brazil. The search was used through survey and critical analysis of the documents published through the search platforms PubMed, Scielo and Lilacs. The following descriptors were used: "Brain death", "diagnosis", "adult" and "electroencephalogram", "Brain death AND electroencephalogram", "Brain death AND Noise AND electroencephalogram", "electroencephalograms AND Brain death" and "Brain death AND electroencephalogram AND intensivecareunits". The opening of the ED protocol should encompass all patients who present themselves as non-perceive, in absence of supra-spinal reactivity and in persistent apnea of known cause, irreversible and capable of causing such end, following a protocol of observation in a hospital environment. To start the protocol opening, it is necessary that there is a brain injury of known cause, irreversible and capable of causing ED, and absence of treatable factors that may confuse the diagnosis, treatment and observation in a hospital environment for the minimum period described, body temperature greater than 35° C, arterial oxygen saturation above 94% and systolic blood pressure greater than or equal to 100 mmHg. Measures are used to assess the level of consciousness, such as the Glasgow scale, as well as tests for the assessment of brain stem activity and the apnea test, which is mandatory for such diagnosis. Among the graphic tests, the electroencephalogram (EEG), cerebral angiography, Doppler Fluxometria transcraniana of cerebral arteries and scintigraphy are extremely relevant, being the EEG considered a feasible method performed at the bedside, low cost and low risk to the patient when compared to scintigraphy and arteriography. For diagnostic purposes in the protocol, the trained physician, with experience, will be responsible for the final report.